2016
DOI: 10.3758/s13414-016-1129-0
|View full text |Cite
|
Sign up to set email alerts
|

All eyes on relevance: strategic allocation of attention as a result of feature-based task demands in multiple object tracking

Abstract: Multiple object tracking (MOT) plays a fundamental role in processing and interpreting dynamic environments. Regarding the type of information utilized by the observer, recent studies reported evidence for the use of object features in an automatic, low-level manner. By introducing a novel paradigm that allowed us to combine tracking with a noninterfering top-down task, we tested whether a voluntary component can regulate the deployment of attention to taskrelevant features in a selective manner. In four exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
(120 reference statements)
2
5
0
Order By: Relevance
“…Results from all experiments revealed some evidence for unequal attention allocation according to strategic top-down control. This is in line with the existing literature documenting top-down, goal-driven attention allocation in MOT (Brockhoff & Huff, 2016) and visual search (Jiang et al, 2015; Navalpakkam et al, 2010; Shomstein & Johnson, 2013). Such findings replicate research demonstrating unequal attention allocation during MOT in response to instructions (Cohen, Pinto, Howe, & Horowitz, 2011; Yantis, 1992), further supporting the efficacy of using goal-directed instructions to manipulate participants’ attention allocation (Bonnel & Miller, 1994; Fitsoul, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from all experiments revealed some evidence for unequal attention allocation according to strategic top-down control. This is in line with the existing literature documenting top-down, goal-driven attention allocation in MOT (Brockhoff & Huff, 2016) and visual search (Jiang et al, 2015; Navalpakkam et al, 2010; Shomstein & Johnson, 2013). Such findings replicate research demonstrating unequal attention allocation during MOT in response to instructions (Cohen, Pinto, Howe, & Horowitz, 2011; Yantis, 1992), further supporting the efficacy of using goal-directed instructions to manipulate participants’ attention allocation (Bonnel & Miller, 1994; Fitsoul, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…This shows that participants modified their tracking strategy in a goal-directed manner. Brockhoff and Huff (2016) combined a typical MOT task with a non-interfering top-down identification task. Participants were instructed to identify the behavior of dynamic cartoon eyes.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the present study may also have implications for our understanding of the attentional mechanisms involved in the MOT paradigm. Several studies have suggested that observers distributed visual attention in a hierarchical manner over the entire display in the MOT task (Brockhoff & Huff, 2016; Doran & Hoffman, 2010; Drew, McCollough, Horowitz, & Vogel, 2009) because the distractors were being processed while the observers were tracking the targets (Alvarez & Oliva, 2008; Brockhoff & Huff, 2016; Doran & Hoffman, 2010; Drew et al, 2009; Meyerhoff, Papenmeier, Jahn, & Huff, 2015, 2016; Tran & Hoffman, 2016). Our hierarchical representation finding is consistent with this idea, which should be considered in future studies of MOT.…”
Section: Discussionmentioning
confidence: 99%
“…When tracking objects with an identity that is irrelevant to the task (the identity is never tested), the question is no longer whether the identity information is processed during tracking. Rather, researchers are more concerned about what kinds of information can be coded and why (Brockhoff & Huff, 2016;Erlikhman et al, 2013;Feria, 2012;Liu et al, 2012;). According to previous studies, both voluntary and involuntary identity processing can be observed in MOT (Erlikhman et al, 2013;Liu et al, 2012;Makovski & Jiang, 2009a, b).…”
Section: Discussionmentioning
confidence: 99%
“…When color category is involved, the case becomes more complex in MOT. First, MOT is a goal-directed task where participants can voluntarily adopt strategies to aid tracking (Brockhoff & Huff, 2016;Feria, 2012). Thus, they may use distinct color labels to name objects when the colors are from different categories and store them in verbal working memory.…”
mentioning
confidence: 99%